Why Did a Five-Year-Old Toddler Become a Victim of Murder? A Criminological and Legal Perspective - Utari, Indah Sri; Arifin, Ridwan; Sabri, Ahmad Zaharuddin Sani Ahmad (Universitas Negeri Semarang (UNNES), 2023)
The tragic and heart-wrenching case of a five-year-old toddler becoming a victim of murder raises numerous questions about the circumstances leading to such a heinous act. This study provides an overview of the factors that might have contributed to this deeply distressing incident. It explores potential reasons, such as family dynamics, societal pressures, mental health issues, and the legal framework surrounding child protection. Understanding the complex interplay of these factors is essential for both preventing similar tragedies in the future and offering appropriate support to affected families. While the global COVID-19 pandemic is gradually receding, reflecting on the past two years reveals a relentless surge in cases that seemed to halt the world momentarily. Amidst the widespread reports of COVID-19 infiltrating Indonesia, the shocking occurrence of a fifteen-year-old taking the life of a five-year-old toddler in Sawah Besar Jakarta in March 2020 deeply unsettled the Indonesian populace. This incident prompts the question: what circumstances led to such a tragic event? What were the motivations driving the perpetrators’ actions? Why did a defenseless five-year-old child fall victim to murder? This study emphasizes the urgency of addressing the root causes of such acts of violence against children, shedding light on the need for comprehensive measures to protect the most vulnerable members of our society.